2023
DOI: 10.1039/d3nr02044d
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow reaction barriers for CO oxidation in Cu–Au nanoclusters

Abstract: Systematic structure prediction of CunAum nanoclusters was carried out for a wide compositional area (m + n ≤ 15) using the evolutionary algorithm USPEX and DFT calculations. The obtained structural...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…[ 49 ] Mikhailova et al predicted the ground‐state structures of Cu n Au m nanoclusters ( n + m ≤ 15) using the USPEX and DFT calculations and proposed that Cu 7 Au 6 cluster is an excellent catalyst for CO oxidation. [ 50 ] By USPEX, a stable and ferromagnetic Fe 17 O 10 − cluster with an accordion‐like structure was predicted, which well explains the prominent mass abundance of Fe 17 O 10 − in the experiment. [ 51 ]…”
Section: Introduction To Existing Cluster Search Methodsmentioning
confidence: 71%
“…[ 49 ] Mikhailova et al predicted the ground‐state structures of Cu n Au m nanoclusters ( n + m ≤ 15) using the USPEX and DFT calculations and proposed that Cu 7 Au 6 cluster is an excellent catalyst for CO oxidation. [ 50 ] By USPEX, a stable and ferromagnetic Fe 17 O 10 − cluster with an accordion‐like structure was predicted, which well explains the prominent mass abundance of Fe 17 O 10 − in the experiment. [ 51 ]…”
Section: Introduction To Existing Cluster Search Methodsmentioning
confidence: 71%
“…For multicomponent systems, such as the considered Li n P m clusters, this criterion can be generalized by calculating the energy differences with respect to the number of atoms of different types and taking the lowest value among them:Δ 2 min ( n , m ) = min{Δ 2 Li E ( n , m ), Δ 2 P E ( n , m )},whereΔ 2 Li E ( n , m ) = E ( n + 1, m ) + E ( n − 1, m ) − 2 E ( n , m ),Δ 2 P E ( n , m ) = E ( n , m + 1) + E ( n , m − 1) − 2 E ( n , m ),and E ( n , m ) is the total energy of the Li n P m cluster ground state. In our previous studies we applied this approach to various multicomponent systems 38,52–55 and found that higher values of Δ 2 min indicate higher abundance of the corresponding clusters or molecules in experiments.…”
Section: Resultsmentioning
confidence: 99%